Design, molecular docking, synthesis and biological evaluation of novel 2,5-substituted imidazole derivatives as anti-inflammatory agents - Akepogu Monalika; M Vijaya Bhargavi (International Journal of Pharma and Bio Sciences, 2020)
Imidazoles have occupied a unique position in heterocyclic chemistry, and its derivatives Imidazoles are heterocyclic compounds which possesses biological and pharmaceutical importance owing to its diversified activities like antibacterial, anti-tumor, antiviral, antiretroviral etc. In the current study 2,5-substituted imidazole were synthesized by using 2-acetyl thiophene as the starting material and 12 derivatives of 2,5- substituted imidazoles were subjected to insilico docking studies (PDB ID:1N26) using AUTODOCK vina software. The compounds that showed the best results were synthesized. The newly synthesized derivatives were characterized using IR, 1H NMR and Mass spectra. All the synthesized derivatives were evaluated for invitro anti-inflammatory activity. The compounds IV c showed good activity whereas compounds IV a ,IV b, IV d, and IV e showed moderate activity which was comparable to that of the standard Diclofenac drug.